EXTH-60. CHARACTERIZATION OF THE ONCOLYTIC ADENOVIRUS DELTA-24-RGD AS THERAPEUTIC AGENT FOR THE TREATMENT OF THE PEDIATRIC EMBRYONAL BRAIN TUMORS AT/RT AND CNS-PNET. (9th November 2020) - Garcia-Moure, Marc; González-Huarriz, Marisol; Laspidea, Virginia; Marrodán, Lucía; Gomez-Manzano, Candelaria; Fueyo, Juan; Patiño-García, Ana; Alonso, Marta M
Abstract: Atypical teratoid/rhabdoid tumors (AT/RTs) and primitive neuroectodermal tumors of the central nervous system (CNS-PNET) are rare pediatric brain tumors affecting mainly infants and young children. Current therapies for these diseases are inefficient and often cause severe side effects; thus, new therapeutic strategies are urgently needed. Here, we evaluate the anti-tumor effect of the Delta-24-RGD oncolytic adenovirus in preclinical models of CNS-PNET and AT/RT. In vitro, the virus infects and efficiently replicates in different cell culture models of AT/RT and CNS-PNET, inducing a dose-dependent cytotoxic effect (IC50 values below 1 PFU/cell) and the release of immunogenic cell death stimuli. Survival studies in mice bearing orthotopic AT/RTs (supra and infratentorial) or CNS-PNETs demonstrate the therapeutic benefit of a single Delta-24-RGD intratumoral administration (10 7 or 10 8 PFU). In virus-treated mice, median overall survival increased between 50–300% (depending on the model), obtaining up to 60% of long-term survivors. Intra-ventricular injection of Delta-24-RGD hinders the development of secondary AT/RT spinal lesions. Moreover, response to the treatment was observed even delaying viral administration up to 30 days after tumor engraftment; thus, demonstrating therapeutic benefit even in animals challenged with large well-established tumor masses. The effect of the oncolytic virus was also assessed in an immunocompetent environment using hCD34+ humanized NSG-SGM3 mice. In this model, Delta-24-RGD significantly extended overall survival (from 23 to 24 days in AT/RT model and from 28 to 55 days in CNS-PNET) with no signs of toxicity associated with inflammation. Immunophenotyping of Delta-24-RGD treated tumors by flow cytometry, RNAseq and multiplexed histology revealed that Delta-24-RGD contributes to generate a pro-inflammatory status, allowing the infiltration of immune cells and the trigger of an antitumor immune response. In conclusion, these results demonstrate that Delta-24-RGD could be a feasible therapeutic choice for AT/RT and CNS-PNET, paving the way for upcoming clinical trials.